Signifikansi Kurikulum Pelayanan Anak Bagi Perkembangan Karakter Anak di Immanuel Kids Community Semarang - Sylvia Margaretha; Dwi Novita Sari (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2025)
Sunday School or what is called children's ministry, is the basis for preparing the church generation in the future. Instilling Biblical values ​​and forming the character of Christ are crucial in teaching Sunday school. That is why the creation of a curriculum as a better teaching program is very necessary. The purpose of this article is primarily to build awareness of the importance of the Sunday school teaching curriculum in order to form children's characters that are similar to Christ. The method used in this study is quantitative with a population of the Immanuel Kids Community Semarang child pastor. The researcher found how the curriculum really helps learning to be more focused and can achieve targets well, so it is recommended that the provision of the curriculum can be immediately applied to Sunday schools in local churches.